Sun Smart Schools Nevada: Increasing Knowledge Among School Children About Ultraviolet Radiation - Kouzes, Emily (Prev Chronic Dis, 2017)
BACKGROUND: Cumulative exposure to ultraviolet radiation (UV) is a risk factor for development of skin cancer. We estimated changes in knowledge, attitudes, and behaviors among Nevada school-age children following implementation of a program to decrease UV exposure. COMMUNITY CONTEXT: The Nevada Cancer Coalition’s Sun Smart Schools pilot program was implemented in 7 Nevada schools during the 2015–2016 school year. The target population was students at participating schools. METHODS: Participation in the program was voluntary. Students surveyed spanned grades from fourth to tenth. Pre-intervention surveys were conducted at the start of the school year. Post-intervention surveys were conducted at the end of the school year. Changes in knowledge, attitudes, and behaviors were assessed among study participants by using self-reported survey responses. OUTCOMES: The Sun Smart Schools pilot program was effective in increasing a broad range of knowledge, attitudes, and behaviors about protection from UV among elementary and middle school students. Students in high school reported an increase in the adoption of selected protective behaviors. However, this population also maintained a positive attitude toward the appearance of tanned skin, indicating susceptibility to competing influences. High school students also did not report any evident change in knowledge about sun protection strategies. Parents reported a decrease in knowledge about UV protection but an increase in adoption of certain protective behaviors. INTERPRETATION: Our findings are similar to those of previous studies demonstrating that education about the dangers of UV exposure is most effective in younger age groups. Results were mixed in older age groups.